History of struggle and improvement of the University of Guayaquil - Villacreses Moscoso, Jorge W. (Revista Universidad de Guayaquil, 1983)
In 1967, the University of Guayaquil celebrated a century of existence, since the University Board was founded and constituted the precursor of what was later the University of Guayaquil, which in the year 1883 was now created, with the true name from the University of Guayaquil, for the same reason, who in 1867 did so under the name of Junta: Don Pedro Carbo. But whether the name is one or the other, the existence of the study corporation has had a history of more than a century of struggles, sacrifices and, what is more, improvement, a process that has led it to be what it is today, one of the great Universities of the Bolivarian countries.